Cook fresh year-round : seasonal recipes from Fine cooking / Fine Cooking - Editors Of Fine Cooking
Packaged in a boxed set of 4 miniature cookbooks for Spring, Summer, Autumn & Winter, this book is suitable for beginner and accomplished cooks. It includes 200 recipes - 50 per season - ideal for the home cook who wants to eat seasonal produce when it's at its peak